Adaptasi 5-item subskala kekerasan seksual pada instrumen Multidimensional Scale Dating Violence (MSDV) - Natanael, Yonathan (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2024)
Research studies using the short version of the MSDV still need to be widely carried out by psychology researchers. To prove the validity of the MSDV in its use in Indonesia, this study aims to conduct a more in-depth investigation of the quality of psychometric properties, especially in the five items of the sexual violence subscale on the MSDV instrument. The research method used is a survey research design. The participants in this study were 171 female students with the criteria of having experienced dating violence, studying at universities, and being domiciled in Jakarta, which were obtained by convenience sampling. This study found that the five items of the sexual violence subscale on the MSDV had the appropriate factor structure, had good reliability values, met the convergence-discriminant validity requirements with the DASS-21 and PMH-Scale instruments, and detectable one item is not invariance. This study implies that the four of five items of the sexual violence subscale are appropriate to use as an instrument for screening dating violence in Indonesia.